3‐D Density Structure of the Lunar Mascon Basins Revealed by a High‐Efficient Gravity Inversion of the GRAIL Data. Issue 5 (11th May 2021) - Zhao, Guangdong; Liu, Jianxin; Chen, Bo; Kaban, Mikhail K.; Du, Jinsong
Abstract: The lunar mascon basins are characterized by high gravity anomalies and thin crust. Study of the density structure beneath the mascon basins can help to understand the origin of these gravity anomalies and infer their formation and evolution. We propose an efficient forward gravity method based on the 3‐D Gauss‐Legendre quadrature (GLQ) and Fast Fourier Transforms combined with the adaptive discretization strategy to ensure high accuracy. The numerical example demonstrates that computational efficiency is increased by about three orders of magnitude compared to the traditional 3D GLQ method. We employ this forward method in a 3‐D inversion of the gravity data derived from the lunar gravity model GL1500E. The inverted results show prominent high‐density structures (namely, mascons) representing significant mantle uplift and thinned crust beneath most impact basins. Marked low‐density rings surround the mascons. Most of the corresponding low‐density anomalies extend from the near‐surface to the Moho, indicating a thick, low‐density crust. Our density model is consistent with the formation processes of mascons that an impact causes collapse of the transient crater and then the shocked mantle drives mantle flow. The low‐density rings surrounding the mascons may stem from the crust thickening following an impact and extensive fracturing of the crustal column. Plain Language Summary: Mascons (i.e., mass concentration) have been found beneath most of the lunar impact basins. Knowledge of their density distribution is vital for understanding of their structure and evolution. The mass excesses in some impact basins extend from the base of the lunar crust to about 60 km depth and correspond to a density anomaly of up to 400 kg/m 3 . These mass concentrations are usually surrounded by a ring of low‐density crust. These features are consistent with the hypothesis that the mascons were formed after an asteroid impact and the upwelling mantle material filling the impact crater. This high‐density material produces the mass excess under the impact basins, while the broken crustal material forms the thick low‐density crust around the mascons. Key Points: A highly efficient forward modeling method for gravity calculations is proposed and used in inversion Prominent high‐density structures represent significant mantle uplift and thinned crust beneath most of the impact basins Negative density anomalies around the mascons form outer rings which may be associated with crustal thickening